View of Mandapa of the Someshwar Mahadev temple - Temples of India Project Team (Jio Institute, 2024)
The mandapa of the Someshwar Mahadev temple is astylar, i.e., bereft of pillars in the centre. It has half-open lateral transepts on either side that allow light to enter the interior.